2022
DOI: 10.1002/jsfa.11942
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early sub‐therapeutic antibiotic administration on body tissue deposition, gut microbiota and metabolite profiles of weaned piglets

Abstract: BACKGROUND This study aimed to evaluate the effects of sub‐therapeutic antibiotic (STA) administration and its subsequent withdrawal on the body tissue deposition, gut microbiota, and metabolite profiles of piglets. The piglets in the experimental group were fed with STA (30 mg kg−1 bacitracin methylene disalicylate, 75 mg kg−1 chlortetracycline, 300 mg kg−1 calcium oxytetracycline) for 14 days and the target bodyweight of the withdrawal period was 25 kg. RESULTS The experiment was divided into two periods: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It has been observed that the use of sub-therapeutic antibiotics in animal feed could significantly increase poultry and livestock productions [ 10 , 11 , 12 ]. The beneficial effects of sub-therapeutic antibiotics as growth promoters include the minimal occurrence of subclinical diseases, the reduction of morbidity and mortality, the increase of daily growth rate, the decrease of feeding costs (require 10–15% less feeding to achieve the desired level of growth), the maximal conversion of feed to animal product, and improvement of reproduction and meat quality (more protein and less fat) [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the use of sub-therapeutic antibiotics in animal feed could significantly increase poultry and livestock productions [ 10 , 11 , 12 ]. The beneficial effects of sub-therapeutic antibiotics as growth promoters include the minimal occurrence of subclinical diseases, the reduction of morbidity and mortality, the increase of daily growth rate, the decrease of feeding costs (require 10–15% less feeding to achieve the desired level of growth), the maximal conversion of feed to animal product, and improvement of reproduction and meat quality (more protein and less fat) [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, improving livestock performance is still an important need for intensive farming [ 1 , 2 ]. Previously, the application of subtherapeutic antibiotics as growth promoters in animal feed has made great achievements [ 3 , 4 , 5 , 6 ]. However, this also leads to a variety of serious antibiotic resistance problems around the world [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%